PENDAFTARAN DAN PERLINDUNGAN HUKUM MEREK DAGANG PADA USAHA AMPLANG DI SAMARINDA - Mia Kusuma Fitriana (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The purpose of the research is to analyze how the trade mark understanding among the amplang producers in Samarinda, the importence of trademark applications, and it’s legal protection that will be earned by registered its trade mark legally. The research was conducted in Samarinda from March to April 2012.The method of the research and it’s analizes will be euseful for the amplang producers in Samarinda. Purposedly to own the legal protections upon the quality of amplang that different with another one produced by anaother. More other it’s legal protections and the economic benefits will be earned from registering the trade mark legally.This research also benefitted for Kantor Wilayah Kementerian Hukum dan HAM Province Kaltim and Direktorat Jenderal Hak Kekayaan Intelektual RI, in order to knowing deeper whethet the socialization toward Trade Mark Law has fully understood by the business doer and other domestic inustries. Thus those institution making a better approach towards the socialization and it’s enforcement.The results of the research showed that the amplang producers in Samarinda lack of valid information related to trade mark applications and the legal protections that will be owned by registering their trade mark legally. Moreover Kanwil Kemenkumham Province Kaltim supposed to be more active doing the socialization toward Trade Mark Law.